(untitled) (Zaporizhzhia Historical Review, 2021)
The article relates the characteristic lines of the politics of the tsar’s government in the sphere of national education in the South of Ukraine in the second half of XIX - beginning of XX century. The author analyses the position of Jewries, Germans, Tatars in the South of Ukraine; defines, that the main constituent of the politics of the government in the in the sphere of national education was russification and shows the basic types of Jewish, German schools and the schools of Tatars of the region.